Flexible and wearable battery-free backscatter wireless communication system for colour imaging - Jun-Lin Zhan; Wei-Bing Lu; Cong Ding; Zhen Sun; Bu-Yun Yu; Lu Ju; Xin-Hua Liang; Zhao-Min Chen; Hao Chen; Yong-Hao Jia; Zhen-Guo Liu; Tie-Jun Cui (npj Flexible Electronics, 2024)
Abstract Wireless imaging, equipped with ultralow power wireless communications and energy harvesting (EH) capabilities, have emerged as battery-free and sustainable solutions. However, the challenge of implementing wireless colour imaging in wearable applications remains, primarily due to high power demands and the need to balance energy harvesting efficiency with device compactness. To address these issues, we propose a flexible and wearable battery-free backscatter wireless communication system specially designed for colour imaging. The system features a hybrid RF-solar EH array that efficiently harvests energy from both ambient RF and visible light energy, ensuring continuous operation in diverse environments. Moreover, flexible materials allow the working system to conform to the human body, ensuring comfort, user-friendliness, and safety. Furthermore, a compact design utilizing a shared-aperture antenna array for simultaneous wireless information and power transfer (SWIPT), coupled with an optically transparent stacked structure. This design not only optimizes space but also maintains the performance of both communication and EH processes. The proposed flexible and wearable systems for colour imaging would have potentially applications in environmental monitoring, object detection, and law enforcement recording. This approach demonstrates a sustainable and practical solution for the next generation of wearable, power-demanding devices.